Cyril of Jerusalem - Yarnold, Edward (Early church fathers., 2000)
This study of the life and works of Cyril, Bishop of Jerusalem, assesses Cyril's thought in the context of fourth-century theological developments and includes up-to-date translations of a selection of his writings.